The Effectiveness of the Qur’anic Reading Guidance Program on Students’ Ability to Read the Qur’an - Azkia Rahmi Afifah; Fauziyah Azizah; Racmelya Salsabila Firdausy; Mokh. Iman Firmansyah; Ega Nasrudin (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
The ability to read the Qur’an serves as a fundamental pillar for comprehending Islamic teachings in their entirety. This study aims to evaluate the effectiveness of the Bina Baca Al-Qur’an (BBQ) program organized by UKM BAQI at the Indonesia University of Education in enhancing students’ Qur’anic reading skills. Employing a quantitative approach, data were collected from pre-test and post-test results involving 42 student samples, complemented by in-depth interviews with program coordinators. Wilcoxon test analysis revealed a statistically significant improvement, with a p-value of < 0.001, confirming the program’s impact in fostering students’ Qur’anic literacy. Key contributing factors include peer-tutoring, teaching strategies, and participants' intrinsic motivation. These findings affirm the value of structured, spiritually grounded interventions within the higher education setting